Penerapan Sistem Akuntansi Pada Perusahaan Steigen - Kania Apriyanti Dwi Putri; Sindi Marsela; Muhamad Faisal Nur Firmansyah; Zahrah Rizqia Syifaania; Mukhlis Joko Wicaksono; Oon Feriyanto (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This study aims to analyze the application of the cash sales, cash receipts, payroll, purchase of raw materials, and inventory of trade goods accounting system at STEIGEN Company. The research employs a qualitative descriptive method with a case study approach, collecting data through observation, interviews, and documentation. The findings indicate that the implementation of the accounting system at STEIGEN Company is inadequate and not in line with generally accepted accounting principles. Based on the study's results, it is recommended that STEIGEN Company makes improvements to the accounting system to optimize operational processes. An in-depth analysis of the cash sales system, cash receipts, payroll, purchase of raw materials, and inventory of trade goods forms the basis for a better understanding of designing, implementing, and maintaining an effective and efficient accounting system in the dynamic business environment.